79 Direct and Indirect Effects of Heat Stress on the Hepatic and Ovarian Proteome in Gilts. (7th May 2021) - Studer, Jamie M; Kiefer, Zoe E; Gianluppi, Rafael; Adur, Malavika K; Schultz, R Blythe; Horst, Erin A; Mayorga, Edith J; Keating, Aileen F; Baumgard, Lance H; Lents, Clay A; Ross, Jason W
Abstract: Seasonal infertility (SI) caused by heat stress (HS) impacts the US swine industry by reducing litter size, farrowing rates, and production efficiency. Identifying the biological underpinnings of SI is a foundational step towards developing mitigation strategies to reduce the nearly 1 billion annual revenue losses to the swine industry. The study objective was to investigate the direct and indirect effects of HS via HS conditioned serum infusion in swine. We hypothesized gilts housed in thermoneutral (TN) conditions receiving gradual infusions of serum obtained from HS gilts would experience altered endocrine and metabolic function compared to gilts receiving serum from TN gilts. Prepubertal gilts (n = 18) were assigned to donor or recipient groups and donors were allocated to TN or HS environments. Blood was collected from HS donors and TN donors exposed to 24-hours of HS or TN conditions, respectively. Serum was infused into recipients housed in TN conditions via indwelling jugular catheters. Over a 24-hour period approximately 20% of the estimated recipient gilt serum volume from donors (pooled by treatment) was infused into recipients. After infusions were completed, gilts were euthanized and tissues collected. Increased rectal temperatures were observed in HS recipients compared to TN recipients (P ≤ 0.05). Protein extracts from liver and ovary underwent proteomic analysis via liquid-chromatography with tandem mass-spectrometry (LC-MS/MS) to assess protein abundance. In the liver and ovary, we identified 135 and 264 proteins, respectively, that were differentially abundant between TN and HS recipients (P < 0.10). Gene Ontology enrichment analysis identified alterations to pathways involved in hormone regulation, immune response, and apoptosis. Collectively, these data demonstrate gilts receiving HS serum experienced altered endocrine and metabolic function compared to gilts receiving TN serum. This project was supported in part by the Iowa Pork Producers Association. USDA is an equal opportunity provider and employer.